Composite solid electrolyte membrane and preparation method thereof, solid-state lithium ion battery

By mixing the first solid electrolyte and the second solid electrolyte and subjecting to hot pressing, a composite solid electrolyte membrane with low porosity is formed, which solves the problem of low density of the existing electrolyte membrane and improves the energy density and safety of the battery .

CN119009145BActive Publication Date: 2025-02-11SUZHOU QINGTAO NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411474056.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-11
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The existing solid electrolyte membrane has low density, which is prone to interface problems and growth of lithium dendrites, resulting in battery short circuits and safety hazards.

Method used

By mixing the first solid electrolyte and the second solid electrolyte and performing hot pressing treatment, the phase state changes of the second solid electrolyte are used to form a continuous state fluid. The first solid electrolyte particles are dispersed therein, and the porosity is prepared after cooling and curing to obtain a relatively high porosity. Low composite solid electrolyte membrane.

Benefits of technology

The density and lithium ion transmission capacity of the composite solid electrolyte membrane are improved, the internal resistance of the battery is reduced, the energy density of the battery is improved, and the risk of lithium dendrites is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119009145B_ABST
    Figure CN119009145B_ABST
Patent Text Reader

Abstract

The present application provides a composite solid electrolyte membrane and a preparation method thereof, and a solid-state lithium-ion battery, which relate to the field of energy storage technology. The preparation method comprises mixing a first solid electrolyte and a second solid electrolyte to obtain a mixture; hot pressing the mixture and cooling it to obtain a composite solid electrolyte membrane; wherein the melting point T2 of the second solid electrolyte is 80°C to 200°C; the hot pressing temperature T0 of the hot pressing treatment is 80°C to 200°C; and satisfies: T0 ≥ T2. The above preparation method can improve the density of the composite solid electrolyte membrane, improve interface problems, reduce interface resistance, inhibit lithium dendrite growth, and improve ionic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage technology, and in particular to a composite solid electrolyte membrane and a preparation method thereof, and a solid-state lithium-ion battery. Background Art

[0002] Solid-state batteries are energy storage elements that can store electrical energy and release it when needed. Compared with traditional liquid batteries, solid-state batteries use solid state electrolytes (SSE) instead of flammable organic liquid electrolytes or gel electrolytes for ion transport, and have higher safety, higher energy density, faster charging speed and longer cycle life.

[0003] The current method for preparing solid electrolyte membranes includes directly pressing a single solid electrolyte particle into a solid electrolyte membrane, or pressing a single solid electrolyte particle into a solid electrolyte membrane after mixing it with a binder such as polytetrafluoroethylene (PTFE). However, due to the defects or gaps between the solid electrolyte particles, the solid electrolyte membrane prepared by the above method has a low density, is prone to interface problems, and causes lithium dendrites to grow through the gaps, which may cause battery short circuits and safety hazards. Summary of the invention

[0004] Based on this, it is necessary to provide a composite solid electrolyte membrane and a preparation method thereof, and a solid-state lithium-ion battery to improve the density of the solid electrolyte membrane.

[0005] In a first aspect, the present application provides a method for preparing a composite solid electrolyte membrane, the method for preparing the composite solid electrolyte membrane comprising:

[0006] mixing a first solid electrolyte and a second solid electrolyte to obtain a mixture;

[0007] Performing hot pressing treatment on the mixture and cooling it to obtain a composite solid electrolyte membrane;

[0008] Wherein, the melting point T2 of the second solid electrolyte is 80°C to 200°C;

[0009] The hot pressing temperature T0 of the hot pressing treatment is 80°C to 200°C;

[0010] And it satisfies: T0≥T2.

[0011] In some embodiments, during the hot pressing step, the second solid electrolyte undergoes a phase change from solid to liquid; and

[0012] In the cooling step, the second solid electrolyte is transformed from a liquid state to a solid state.

[0013] In some embodiments, in the hot pressing step, the hot pressing temperature T0 and the melting point T1 of the first solid electrolyte satisfy: T1>T0.

[0014] In some embodiments, in the hot pressing step, the hot pressing time of the hot pressing treatment is 0.5 min to 30 min; and / or,

[0015] The hot pressing pressure of the hot pressing treatment is 10MPa~500MPa.

[0016] In some embodiments, during the cooling step, the mixture is cooled naturally at room temperature.

[0017] In some embodiments, the step of mixing the first solid electrolyte and the second solid electrolyte specifically includes weighing the first solid electrolyte and the second solid electrolyte according to a mass ratio, and the mass ratio of the first solid electrolyte to the second solid electrolyte is (95:5) to (20:80).

[0018] In some preferred embodiments, the step of mixing the first solid electrolyte and the second solid electrolyte specifically includes weighing the first solid electrolyte and the second solid electrolyte according to a mass ratio, and the mass ratio of the first solid electrolyte to the second solid electrolyte is (70:30) to (45:55).

[0019] In some embodiments, in the step of mixing the first solid electrolyte and the second solid electrolyte, the ratio of the particle size D50 of the first solid electrolyte to the particle size D50 of the second solid electrolyte is (1:5) to (10:1).

[0020] In some preferred embodiments, in the step of mixing the first solid electrolyte and the second solid electrolyte, the ratio of the particle size D50 of the first solid electrolyte to the particle size D50 of the second solid electrolyte is (2:1) to (4:1).

[0021] In some embodiments, in the step of mixing the first solid electrolyte with the second solid electrolyte, the second solid electrolyte comprises Li3MCl 6-x Br x , M is a trivalent metal ion, and x satisfies 0<x<6.

[0022] In some embodiments, the second solid electrolyte comprises Li3MCl 6-x Br x , M is a trivalent metal ion, and x satisfies 2≤x≤5.

[0023] In some embodiments, M is selected from Ga3+ 、In 3+ 、Al 3+ , Fe 3+ , Y 3+ 、Bi 3+ , one or more of the +3 valent lanthanide metals.

[0024] In some embodiments, the mixing method of the first solid electrolyte and the second solid electrolyte is ball milling, and the ball milling meets at least one of the following conditions (1) to (3):

[0025] (1) The rotation speed of the ball milling mixing is 100 rpm to 300 rpm;

[0026] (2) The ball milling mixing time is 0.1h~2h;

[0027] (3) The ball-to-material ratio of the ball milling mixture is (3:1) to (30:1).

[0028] In a second aspect, the present application further provides a composite solid electrolyte membrane, which is a composite solid electrolyte membrane prepared by the preparation method provided in the first aspect of the present application.

[0029] In some embodiments, the porosity of the composite solid electrolyte membrane is 0.1% to 10%.

[0030] In some embodiments, the composite solid electrolyte membrane has a thickness of 10 μm to 100 μm.

[0031] In a third aspect, the present application also provides a solid-state lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, and a composite solid electrolyte membrane provided in the second aspect of the present application located between the positive electrode sheet and the negative electrode sheet, or a composite solid electrolyte membrane prepared by the preparation method provided in the first aspect of the present application.

[0032] In the above-mentioned composite solid electrolyte membrane preparation method, the first solid electrolyte and the second solid electrolyte are mixed to obtain a mixture, and then the mixture is hot-pressed to obtain a composite solid electrolyte, the melting point of the second solid electrolyte is less than or equal to the hot-pressing temperature, the second solid electrolyte is melted to form a continuous fluid under a certain pressure, the first solid electrolyte particles are dispersed therein, and after cooling and solidification, a composite solid electrolyte membrane with low porosity is prepared. Compared with the method of directly pressing solid electrolyte particles to form a solid electrolyte membrane, in the present application, the phase change of the second solid electrolyte makes the combination between the first solid electrolyte and the second solid electrolyte in the composite solid electrolyte membrane more compact, which is beneficial to reducing the porosity of the composite solid electrolyte membrane, and is also beneficial to achieving good composite of the first solid electrolyte and the second solid electrolyte in a state of low binder usage or no binder. At the same time, since both the first solid electrolyte and the second solid electrolyte have lithium ion transmission capabilities, it is beneficial to improve the lithium ion transmission capability of the composite solid electrolyte membrane as a whole, thereby effectively reducing the battery internal resistance of the solid-state battery using the composite solid electrolyte membrane and improving the energy density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The present invention is a flow chart of a method for preparing a composite solid electrolyte membrane in one embodiment of the present application. DETAILED DESCRIPTION

[0034] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0035] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0036] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0037] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0038] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0039] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0040] If there is no special explanation, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps S12 and S14, which means that the method may include steps S12 and S14 performed sequentially, or may include steps S14 and S12 performed sequentially. For example, it is mentioned that the method may also include step S16, which means that step S16 may be added to the method in any order, for example, the method may include steps S12, S14 and S16, or may include steps S12, S16 and S14, or may include steps S16, S12 and S14, etc.

[0041] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0042] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0043] The current solid electrolyte membrane is limited by the defects of solid electrolyte particles or the gaps between particles, and has a low density. The lithium deposition / stripping caused by the uneven electric field and ion distribution at the interface can easily cause a huge volume change of the lithium metal electrode material. Local excessive lithium deposition / stripping will lead to the continuous renewal of the electrolyte membrane and electrode interface, resulting in the continuous occurrence of interfacial reactions and the continuous increase of interfacial impedance. In addition, due to the uneven deposition of lithium ions on the electrode surface, lithium dendrites are easily grown, which usually occurs on lithium metal negative electrodes. The low density of the solid electrolyte membrane causes lithium dendrites to grow through the gaps, so that the lithium metal negative electrode penetrates into the electrolyte during the lithium metal battery cycle, which may cause battery short circuits and safety hazards.

[0044] When preparing solid electrolyte membranes, traditional technology can improve interface performance by reducing the particle size of solid electrolyte particles. However, the reduction in the particle size of solid electrolyte particles will lead to a decrease in the ionic conductivity of the solid electrolyte membrane, and its improvement on density is not obvious.

[0045] like Figure 1 As shown, the first aspect of the embodiment of the present application provides a method for preparing a composite solid electrolyte membrane, the preparation method comprising the following steps:

[0046] S1. Mix the first solid electrolyte and the second solid electrolyte to obtain a mixture.

[0047] The embodiments of the present application do not specifically limit the types of the first solid electrolyte and the second solid electrolyte. Any known solid electrolyte can be used in the present application without violating the inventive concept of the present application. As an illustrative example only, not a limitation on the scope of protection, the first solid electrolyte includes but is not limited to one or more of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, and a polymer solid electrolyte.

[0048] The embodiment of the present application does not specifically limit the mixing method of the first solid electrolyte and the second solid electrolyte. Any known mixing method can be used in the present application without violating the inventive concept of the present application. As an illustrative example only, not a limitation on the scope of protection, the mixing method includes but is not limited to ball milling, air flow mixing or pulverizer.

[0049] S2. The mixture is subjected to hot pressing treatment and cooled to obtain a composite solid electrolyte membrane.

[0050] The melting point T2 of the second solid electrolyte is 80°C to 200°C, the hot pressing temperature T0 of the mixture during hot pressing is 80°C to 200°C, and T0≥T2 is satisfied.

[0051] The preparation method of the above-mentioned composite solid electrolyte membrane comprises the following steps: composite a first solid electrolyte and a second solid electrolyte having a melting point in the range of 80°C to 200°C, mixing the first solid electrolyte and the second solid electrolyte to obtain a mixture, and then hot pressing and cooling the mixture to obtain a composite solid electrolyte membrane. The melting point of the second solid electrolyte is less than or equal to the hot pressing temperature. After the second solid electrolyte is melted, it forms a continuous fluid under a certain pressure, and the first solid electrolyte particles are dispersed therein. After cooling and solidification, a composite solid electrolyte membrane with low porosity is prepared.

[0052] At the same time, by utilizing the phase change of the second solid electrolyte, the bonding between the first solid electrolyte and the second solid electrolyte in the composite solid electrolyte membrane is made tighter, which is beneficial to achieving a good composite of the first solid electrolyte and the second solid electrolyte with a lower binder usage or in the absence of a binder. In addition, since both the first solid electrolyte and the second solid electrolyte have lithium ion transmission capabilities, it is beneficial to improve the overall lithium ion transmission capacity of the composite solid electrolyte membrane. Therefore, the internal resistance of the solid-state battery using the composite solid electrolyte membrane can be effectively reduced, thereby improving the energy density of the battery.

[0053] In some embodiments, during the step of subjecting the mixture to hot pressing, the second solid electrolyte undergoes a phase change from solid to liquid, and during the cooling step, the second solid electrolyte changes from liquid to solid.

[0054] The second solid electrolyte of the embodiment of the present application may be a granular dispersed phase rather than a continuous phase before hot pressing treatment. During the hot pressing process, the second solid electrolyte undergoes a phase change at a certain temperature and pressure, from a granular dispersed phase to a liquid phase with fluidity, and the liquid phase forms a continuous state. Then, during the cooling process, a phase change occurs again, and the second solid electrolyte changes from a liquid state to a solid state, forming a solid continuous structure.

[0055] In this way, the first solid electrolyte can be embedded or distributed in the solid continuous structure of the second solid electrolyte in a dispersed manner, so that the first solid electrolyte and the second solid electrolyte are more closely combined, thereby improving the overall density of the prepared composite solid electrolyte membrane. At the same time, the continuous solid structure of the second solid electrolyte in the composite solid electrolyte membrane can provide a more uniform and stable ion conduction path, further effectively improving the lithium ion transmission capacity of the composite solid electrolyte membrane.

[0056] In some embodiments, in the step of hot pressing the mixture, the hot pressing temperature T0 and the melting point T2 of the second solid electrolyte and the melting point T1 of the first solid electrolyte satisfy T1>T0≥T2.

[0057] The melting point of the first solid electrolyte of the embodiment of the present application is greater than the hot pressing temperature, so that when the mixture of the first solid electrolyte and the second solid electrolyte is hot pressed, the first solid electrolyte can remain solid and will not melt, so that the first solid electrolyte layer can maintain its inherent structure and performance, ensuring a certain mechanical strength and pore structure. The second solid electrolyte in liquid form can effectively penetrate into the microstructure of the solid first solid electrolyte layer, enhance the bonding force between the two, and thus improve the overall performance of the composite solid electrolyte membrane.

[0058] In some embodiments, in the step of hot pressing the mixture, the time of hot pressing is 0.5min~30min, including but not limited to 0.5min, 1min, 2min, 3min, 4min, 5min, 6min, 8min, 10min, 12min, 14min, 15min, 16min, 18min, 20min, 25min, 30min or other values ​​satisfying the above range. In this way, the second solid electrolyte can flow within a certain period of time and has a suitable flow range. When it can flow to form a continuous structure, it will not cause excessive loss of the second solid electrolyte, thereby ensuring the conductivity of lithium ions.

[0059] In some embodiments, in the step of hot pressing the mixture, the pressure of the hot pressing is 10MPa~500MPa, including but not limited to 10MPa, 20MPa, 30MPa, 40MPa, 50MPa, 60MPa, 70MPa, 80MPa, 90MPa, 100MPa, 150MPa, 200MPa, 250MPa, 300MPa, 350MPa, 400MPa, 450MPa, 500MPa or other values ​​satisfying the above range. In this way, the hot pressing pressure can promote the flow of the second solid electrolyte within a suitable range without destroying the structure of the first solid electrolyte or causing unnecessary side reactions.

[0060] In some embodiments, in the cooling step of cooling to obtain the composite solid electrolyte membrane, the mixture treated by hot pressing is naturally cooled at room temperature. In this way, during the natural cooling process, the second solid electrolyte slowly solidifies from the liquid state, providing sufficient time for the interface bonding between the first solid electrolyte and the second solid electrolyte, and the first solid electrolyte can be better dispersed or filled in the continuous structure of the second solid electrolyte, thereby improving the bonding force between the two, thereby improving the density and mechanical strength of the composite electrolyte membrane. At the same time, the natural cooling method can avoid uneven shrinkage that may be caused by excessive cooling, reduce the accumulation of thermal stress, and ensure the overall structural integrity of the composite solid electrolyte membrane.

[0061] In some embodiments, the step of mixing the first solid electrolyte and the second solid electrolyte specifically includes weighing the first solid electrolyte and the second solid electrolyte according to the mass ratio, wherein the mass ratio of the first solid electrolyte to the second solid electrolyte is (95:5) to (20:80), including but not limited to (95:5), (90:10), (85:15), (80:20), (75:25), (70:30), (65:35), (60:40), (55:45), (50:50), (45:55), (40:60), (35:65), (30:70), (25:75), (20:80) or other values ​​satisfying the above range. Preferably, the mass ratio of the first solid electrolyte to the second solid electrolyte can be (80:20) to (35:65), and better still, the mass ratio of the first solid electrolyte to the second solid electrolyte can be (70:30) to (45:55).

[0062] In this way, with an appropriate mass ratio of the first solid electrolyte and the second solid electrolyte, on the one hand, the fluid formed by the second solid electrolyte transforming from solid to liquid during the hot pressing process of the mixture can fill the tiny gaps in the composite electrolyte system, reduce the porosity of the prepared composite solid electrolyte membrane, and then effectively improve the density of the prepared composite solid electrolyte membrane, thereby reducing the risk of lithium dendrite growth. On the other hand, the appropriate mass of the first solid electrolyte can effectively enhance the mechanical strength of the composite solid electrolyte membrane and prevent the composite solid electrolyte from being crushed during a long period of charge and discharge cycle.

[0063] In some embodiments, in the step of mixing the first solid electrolyte and the second solid electrolyte, the ratio of the particle size D50 of the first solid electrolyte to the particle size D50 of the second solid electrolyte is (1:5) to (10:1), including but not limited to (1:5), (1:4), (1:3), (1:2), (1:1), (2:1), (3:1), (4:1), (5:1), (6:1), (7:1), (8:1), (9:1), (10:1) or other values ​​satisfying the above range. Preferably, the ratio of the particle size D50 of the first solid electrolyte to the particle size D50 of the second solid electrolyte is (1:2) to (6:1), and more preferably, the ratio of the particle size D50 of the first solid electrolyte to the particle size D50 of the second solid electrolyte is (2:1) to (4:1).

[0064] In this way, when the first solid electrolyte and the second solid electrolyte are mixed, the two particles can better fill and interlock with each other during the mixing process, making the mixture more uniform. In addition, when the mixture of the two is subjected to hot pressing, compared to the second solid electrolyte, the particle size of the first solid electrolyte is within a suitable range, the gap volume formed by the two is moderate, and the second solid electrolyte can be effectively connected to the first solid electrolyte after melting or partial melting. Compared to the first solid electrolyte, the particle size of the second solid electrolyte is within a suitable range, the second solid electrolyte can melt faster to form a continuous structure and provide a stable matrix, so that the first solid electrolyte is dispersed thereon to form a tightly bound composite structure.

[0065] In some embodiments, in the step of mixing the first solid electrolyte with the second solid electrolyte, the second solid electrolyte comprises Li3MCl 6-x Br x , M is a trivalent metal ion, x satisfies 0<x<6, more preferably, x satisfies 2≤x≤5, and x can be but is not limited to 2, 3, 4, 5.

[0066] The second solid electrolyte of the embodiment of the present application includes a solid electrolyte obtained by doping and modifying the Li3MCl6 basic halide solid electrolyte with the halogen element Br. By replacing some chloride ions in Li3MCl6 with bromide ions with lower electronegativity and larger ionic radius, the strength of the ionic bond can be weakened, and the melting point of the electrolyte material can be reduced, so that the initial second solid electrolyte of the raw material can be partially or completely melted at a lower temperature (80°C~200°C) to form a continuous state, and then a second solid electrolyte with a continuous structure is formed after phase change and solidification.

[0067] In addition, bromide ions with a larger ionic radius replace some chloride ions in the electrolyte, increase the voids in the lattice or reduce the rigidity of the lattice, reduce the constraints on lithium ions, thereby facilitating the migration of lithium ions and improving the ionic conductivity of the composite solid electrolyte membrane. Bromide ions also have lower electronegativity, which helps to reduce side reactions between the electrolyte and the electrode material, thereby improving the stability of the interface and extending the cycle life of the solid-state battery using the composite solid electrolyte.

[0068] In some embodiments, M is selected from Ga 3+ 、In 3+ 、Al 3+ , Fe 3+ , Y 3+ Sc 3+ 、Bi 3+ and one or more of trivalent lanthanide metal ions.

[0069] It should be noted that M may include one metal ion or multiple metal ions. For example, M includes two metal ions, assuming that they are A ions and B ions, and the second solid electrolyte may be Li3A y B z Cl 6-x Br x , the valence of element A is a, the valence of element B is b, and they satisfy ay+bz=3.

[0070] As an example, the second solid electrolyte is not limited to Li3Y 0.5 Dy 0.5 Cl3Br3、Li3Y 0.5 Dy 0.5 Cl4Br2、Li3Y 0.5 Dy 0.5 Cl5Br1、Li3Y 0.5 Dy 0.5 Cl2Br4、Li3Y 0.5 Dy 0.5 Cl1Br5、Li3Y 0.5 Fe 0.5 Cl1Br5、Li3Dy 0.5 Al 0.5 One or more of Cl1Br5. Preferably, the second solid electrolyte comprises Li3Y 0.5 Dy 0.5 Cl3Br3.

[0071] In some embodiments, the melting point of the second solid electrolyte ranges from 80°C to 200°C, and the melting point of the second solid electrolyte includes but is not limited to 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C or other values ​​satisfying the above range. As an example, Li3Y 0.5 Dy 0.5 The melting point of Cl3Br3 is 120℃, Li3Y 0.5 Fe 0.5 The melting point of Cl1Br5 is 125°C, and the melting point of Li3InCl3Br3 is 120°C. In this way, during the hot pressing process, the second solid electrolyte melts and has fluidity, forming a continuous structure, in which the first solid electrolyte particles are dispersed. After cooling and solidification, a composite solid electrolyte membrane with low porosity is prepared, which improves the density and interface performance, inhibits the penetration of lithium dendrites into the positive electrode, and improves the ionic conductivity of the solid electrolyte membrane.

[0072] In some embodiments, the first solid electrolyte includes an inorganic solid electrolyte, preferably a halide solid electrolyte, and the ionic conductivity of the halide solid electrolyte is higher than that of other types of solid electrolytes. Further, a halide solid electrolyte material with high flexibility and excellent deformation ability can be preferably selected. As an example, the halide solid electrolyte material includes Li 1.75 ZrCl 4.75 O 0.5 , Li 2.25 Zr 0.75 Dy 0.25 Cl 4.5 O 0.75 Thus, during the mixing and hot pressing process, the first solid electrolyte can achieve a better and tighter fit with the second solid electrolyte, further improving the density of the composite solid electrolyte membrane.

[0073] In some optional embodiments, the first solid electrolyte may also include an oxide solid electrolyte material, such as NASICON (Na + Super Ionic Conductor) solid electrolyte lithium aluminum germanium phosphate (LAGP, Li 1.5 Al 0.5 Ge 1.5 (PO4)3), NASICON solid electrolyte lithium aluminum titanium phosphate (LATP, Li 1.3 Al 0.3 Ti 1.7 (PO4)3), garnet-type solid electrolyte lanthanum lithium zirconate (LLZO, Li7La3Zr2O 12 ) and perovskite-type solid electrolyte lithium lanthanum titanate (LLTO, Li 0.5 La 0.5 TiO3) or more.

[0074] In some embodiments, the mixing method of mixing the first solid electrolyte and the second solid electrolyte includes ball milling mixing. As an example, the mixing device is a ball milling jar, and further, the mixing device is a ZrO2 ball milling jar.

[0075] In some optional embodiments, the rotation speed of ball milling is 100rpm~300rpm, including but not limited to 100rpm, 120rpm, 140rpm, 160rpm, 180rpm, 200rpm, 220rpm, 240rpm, 260rpm, 280rpm, 300rpm or other values ​​satisfying the above range. In this way, the rotation speed of 100rpm~300rpm provides moderate mixing energy for ball milling, and the first solid electrolyte and the second solid electrolyte particles can be effectively dispersed during the mixing process, ensuring that the two materials are evenly distributed in the mixture, while maintaining the morphology of the solid electrolyte particles and maintaining a reasonable particle size distribution.

[0076] In some optional embodiments, the ball milling mixing time is 0.1h~2h, including but not limited to 0.1h, 0.2h, 0.4h, 0.6h, 0.8h, 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h or other values ​​satisfying the above range. In this way, by setting the time range of 0.1h~2h, it can be ensured that the particles of the first solid electrolyte and the second solid electrolyte can be evenly distributed, while preventing the solid electrolyte particles from being subjected to excessive impact and friction.

[0077] In some optional embodiments, the ball-to-material ratio of ball milling is (3:1) to (30:1), including but not limited to (3:1), (5:1), (8:1), (10:1), (15:1), (20:1), (25:1), (30:1) or other values ​​satisfying the above range. In this way, the mixing process can be accelerated by an appropriate ball-to-material ratio, so that the solid electrolyte particles are dispersed in the mixture more quickly and evenly, thereby improving the mixing efficiency, while avoiding excessive mechanical action leading to particle breakage or excessive material wear.

[0078] The second aspect of the embodiment of the present application further provides a composite solid electrolyte membrane, which is prepared by the preparation method provided by the first aspect of the embodiment of the present application.

[0079] In some embodiments, the porosity of the composite solid electrolyte membrane is 0.1%-10%, and the porosity of the composite solid electrolyte membrane can be, but is not limited to, 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% or other values ​​satisfying the above range. Within the above range, the composite solid electrolyte membrane has good lithium ion transmission capacity. On the other hand, the above porosity is achieved by mixing the first solid electrolyte and the second solid electrolyte and hot pressing, and the first solid electrolyte is dispersed in the continuous structure formed by the second solid electrolyte. Further, the porosity of the composite solid electrolyte membrane can be 0.3%~6%, more preferably 0.5%~3%.

[0080] In some embodiments, the thickness of the composite solid electrolyte membrane is 10 μm-100 μm, and the thickness of the composite solid electrolyte membrane includes but is not limited to 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm or other values ​​satisfying the above range. Preferably, the thickness of the composite solid electrolyte membrane is 20-50 μm. Within the above range, the composite solid electrolyte membrane can reduce the resistance to ion migration, improve ion conductivity, and provide more ion storage space. The solid-state lithium-ion battery using the composite solid electrolyte membrane can take into account both high cycle performance and the energy density of the overall battery.

[0081] The third aspect of the embodiment of the present application further provides a solid-state lithium-ion battery, including a positive electrode sheet, a negative electrode sheet, and a composite solid electrolyte membrane located between the positive electrode sheet and the negative electrode sheet. The relevant contents of the composite solid electrolyte membrane can be referred to the above introduction, and will not be repeated here.

[0082] In the embodiment of the present application, the positive electrode plate includes a positive electrode collector and a positive electrode active electrode material layer formed on the current collector, and the negative electrode plate includes a negative electrode collector and a negative electrode active electrode material layer formed on the negative electrode collector.

[0083] The positive electrode active material layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductive material. The positive electrode active material is a compound that enables lithium to be reversibly embedded and de-embedded, specifically, it may include a layered oxide positive electrode, a spinel positive electrode, an olivine-type positive electrode and a polyanion positive electrode, sulfur and its compounds. Preferably, the mass proportion of the positive electrode active material contained in the positive electrode active material layer can be 80wt%-99wt%, such as 80wt%, 82wt%, 85wt%, 87wt%, 90wt%, 92wt%, 95wt%, 97wt%, 99wt%, etc., preferably 92wt%-98.5wt%.

[0084] The positive electrode binder is used to bind the components such as the positive electrode active material, the positive electrode conductive material and the positive electrode current collector together. Specifically, the positive electrode binder may include at least one selected from polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, styrene-butadiene rubber and fluororubber, preferably polyvinylidene fluoride. The mass proportion of the positive electrode binder contained in the positive active electrode material layer may be 1wt%-20wt%, such as 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, etc., preferably 1.2wt%-10wt%.

[0085] The positive electrode conductive material is mainly used to assist and improve the conductivity in the secondary battery, and there is no particular limitation on it in the embodiments of the present application, as long as it has conductivity without causing chemical changes. Specifically, the positive electrode conductive material may include graphite, and the mass proportion of the positive electrode conductive material contained in the positive active electrode material layer may be 1wt%-20wt%, such as 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, etc., preferably 1.2wt%-10wt%.

[0086] There is no particular limitation on the negative electrode active material in the embodiments of the present application, as long as it is a material that can electrochemically absorb and release S-zone metal ions such as lithium ions, sodium ions, potassium ions, and magnesium ions, such as carbonaceous materials, metal compound materials, or their oxides, carbides, nitrides, silicides, sulfides, phosphides, etc. These materials can be used alone, or two or more of them can be used in combination.

[0087] In order to explain the technical content, structural features, achieved objectives and effects of the technical solutions of the embodiments of the present application in detail, the following is a detailed description in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.

[0088] Example 1

[0089] (1) Composite solid electrolyte membrane

[0090] The first solid electrolyte Li 2.25 Zr 0.75 Dy 0.25 Cl 4.5 O 0.75 and the second solid electrolyte Li3Y 0.5 Dy 0.5 Cl3Br3 was added to a ball mill in a glove box in a mass ratio of 1:1, wherein the melting point of the first solid electrolyte was 350°C, the melting point of the second solid electrolyte was 120°C, the particle size D90 of the first solid electrolyte was 0.9 μm, the particle size D90 of the second solid electrolyte was 0.3 μm, and the ratio of the particle size D50 of the first solid electrolyte to the particle size D50 of the second solid electrolyte was 3:1.

[0091] Add ball milling beads into the ball milling jar at a ball-to-material ratio of 10:1, then put the ball milling jar into a high-energy ball mill and perform high-energy ball milling at a speed of 200 rpm for 30 minutes to obtain a mixture.

[0092] The mixture was placed in a hot pressing mold and hot pressed for 10 minutes at a pressure of 100 MPa and a temperature of 160° C. to obtain a composite solid electrolyte membrane.

[0093] (2) Preparation of positive electrode

[0094] NCM811, PTFE, super-P, and Li2ZrCl6 were mixed evenly in a mass ratio of 70:3:2:25, placed in a high shear force equipment mixer, subjected to fiberization treatment, and formed a first mixed material, which was rolled to form a first positive electrode layer; the rolling temperature was 60°C, and the rolling time was 5 minutes; the positive electrode current collector and the first positive electrode layer were stacked, hot pressed, and cooled to form a composite positive electrode. The hot pressing temperature was 150°C, the time was 10 minutes, and the pressure was 120Mpa.

[0095] (3) Preparation of negative electrode

[0096] The negative electrode active materials graphite, (CMC+SBR), super-P and Li3YCl3Br3 are mixed evenly in a mass ratio of 69:4:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a second mixture, which is then rolled to form a first negative electrode layer; the rolling temperature is 60°C and the rolling time is 5 minutes; the negative electrode current collector and the first negative electrode layer are stacked, hot-pressed, and cooled to form a composite negative electrode. The hot-pressing temperature is 120°C, the time is 12 minutes, and the pressure is 200MPa.

[0097] (4) Preparation of solid-state lithium-ion batteries

[0098] The positive electrode sheet, composite solid electrolyte membrane and negative electrode sheet are stacked and packaged to form a solid-state lithium-ion battery.

[0099] Example 2

[0100] The preparation method of Example 2 is basically the same as that of Example 1, except that: the first solid electrolyte Li 2.25 Zr 0.75 Dy 0.25 Cl 4.5 O 0.75 and the second solid electrolyte Li3Y 0.5 Dy 0.5 The mass ratio of Cl3Br3 is 95:5, that is, the first solid electrolyte Li 2.25 Zr 0.75 Dy 0.25 Cl 4.5 O 0.75 and the second solid electrolyte Li3Y 0.5 Dy 0.5 Cl3Br3 was added into a ball mill in a glove box at a mass ratio of 95:5, and the rest was the same as in Example 1.

[0101] Example 3

[0102] The preparation method of Example 3 is basically the same as that of Example 1, except that: the first solid electrolyte Li 2.25 Zr 0.75 Dy 0.25 Cl 4.5 O 0.75 and the second solid electrolyte Li3Y 0.5 Dy 0.5 The mass ratio of Cl3Br3 is 20:80, that is, the first solid electrolyte Li 2.25 Zr 0.75 Dy 0.25 Cl 4.5 O 0.75 and the second solid electrolyte Li3Y 0.5 Dy 0.5 Cl3Br3 was added into a ball mill in a glove box at a mass ratio of 20:80, and the rest was the same as in Example 1.

[0103] Example 4

[0104] The preparation method of Example 4 is basically the same as the preparation method of Example 1, except that the particle size D90 of the first solid electrolyte is 0.06 μm, the particle size D90 of the second solid electrolyte is 0.3 μm, and the ratio of the particle size D50 of the first solid electrolyte to the particle size D50 of the second solid electrolyte is 1:5.

[0105] Example 5

[0106] The preparation method of Example 5 is basically the same as the preparation method of Example 1, except that the particle size D90 of the first solid electrolyte is 0.9 μm, the particle size D90 of the second solid electrolyte is 0.09 μm, and the ratio of the particle size D50 of the first solid electrolyte to the particle size D50 of the second solid electrolyte is 10:1.

[0107] Example 6

[0108] The preparation method of Example 6 is basically the same as the preparation method of Example 1, except that the hot pressing temperature is 120°C, that is, the mixture is placed in a hot pressing mold, and hot pressing is continued for 10 minutes under a pressure of 100 MPa and a temperature of 120°C to obtain a composite solid electrolyte membrane. The rest is the same as Example 1.

[0109] Example 7

[0110] The preparation method of Example 7 is basically the same as the preparation method of Example 1, except that the hot pressing temperature is 200°C, that is, the mixture is placed in a hot pressing mold, and hot pressing is continued for 10 minutes under a pressure of 100 MPa and a temperature of 200°C to obtain a composite solid electrolyte membrane. The rest is the same as Example 1.

[0111] Example 8

[0112] The preparation method of Example 8 is basically the same as the preparation method of Example 1, except that the hot pressing time is 0.5 min, that is, the mixture is placed in a hot pressing mold, and hot pressing is continued for 0.5 min under a pressure of 100 MPa and a temperature of 160°C to obtain a composite solid electrolyte membrane. The rest is the same as Example 1.

[0113] Example 9

[0114] The preparation method of Example 9 is basically the same as the preparation method of Example 1, except that the hot pressing time is 30 minutes, that is, the mixture is placed in a hot pressing mold, and hot pressing is continued for 30 minutes under a pressure of 100 MPa and a temperature of 160°C to obtain a composite solid electrolyte membrane. The rest is the same as Example 1.

[0115] Example 10

[0116] The preparation method of Example 10 is basically the same as the preparation method of Example 1, except that the hot pressing pressure is 10 MPa, that is, the mixture is placed in a hot pressing mold, and hot pressing is continued for 10 minutes under an environment of pressure of 10 MPa and temperature of 160°C to obtain a composite solid electrolyte membrane. The rest is the same as Example 1.

[0117] Embodiment 11

[0118] The preparation method of Example 11 is basically the same as the preparation method of Example 1, except that the hot pressing pressure is 500 MPa, that is, the mixture is placed in a hot pressing mold, and hot pressing is continued for 10 minutes under a pressure of 500 MPa and a temperature of 160°C to obtain a composite solid electrolyte membrane. The rest is the same as Example 1.

[0119] Example 12

[0120] The preparation method of Example 12 is basically the same as the preparation method of Example 1, except that: the rotation speed of ball milling mixing is 100 rpm, that is, ball milling beads are added to the ball mill jar at a ball-to-material ratio of 10:1, and then the ball mill jar is placed in a high-energy ball mill and high-energy ball milling is performed at a rotation speed of 100 rpm for 30 minutes to obtain a mixture. The rest is the same as Example 1.

[0121] Embodiment 13

[0122] The preparation method of Example 13 is basically the same as the preparation method of Example 1, except that: the rotation speed of ball milling mixing is 300 rpm, that is, ball milling beads are added to the ball mill jar at a ball-to-material ratio of 10:1, and then the ball mill jar is placed in a high-energy ball mill and high-energy ball milling is performed at a rotation speed of 300 rpm for 30 minutes to obtain a mixture. The rest is the same as Example 1.

[0123] Embodiment 14

[0124] The preparation method of Example 14 is basically the same as the preparation method of Example 1, except that: the ball milling mixing time is 6 minutes, that is, ball milling beads are added to the ball mill jar at a ball-to-material ratio of 10:1, and then the ball mill jar is placed in a high-energy ball mill and high-energy ball milling is performed at a speed of 200 rpm for 6 minutes to obtain a mixture. The rest is the same as Example 1.

[0125] Embodiment 15

[0126] The preparation method of Example 15 is basically the same as the preparation method of Example 1, except that: the ball milling mixing time is 120 minutes, that is, ball milling beads are added to the ball milling jar at a ball-to-material ratio of 10:1, and then the ball milling jar is placed in a high-energy ball mill and high-energy ball milling is performed at a speed of 200 rpm for 120 minutes to obtain a mixture. The rest is the same as Example 1.

[0127] Example 16

[0128] The preparation method of Example 16 is basically the same as the preparation method of Example 1, except that the ball-to-material ratio of the ball-milling mixture is 3:1, that is, ball milling beads are added to the ball mill jar according to the ball-to-material ratio of 3:1, and then the ball mill jar is placed in a high-energy ball mill and high-energy ball milling is performed at a speed of 200 rpm for 30 minutes to obtain a mixture. The rest is the same as Example 1.

[0129] Embodiment 17

[0130] The preparation method of Example 17 is basically the same as the preparation method of Example 1, except that the ball-to-material ratio of the ball-milling mixture is 30:1, that is, ball milling beads are added to the ball mill jar according to the ball-to-material ratio of 30:1, and then the ball mill jar is placed in a high-energy ball mill and high-energy ball milling is performed at a speed of 200 rpm for 30 minutes to obtain a mixture. The rest is the same as Example 1.

[0131] Comparative Example 1

[0132] The preparation method of comparative example 1 is basically the same as that of embodiment 1, except that: the second solid electrolyte is Li3YCl6, that is, the first solid electrolyte Li 2.25 Zr 0.75 Dy 0.25 Cl 4.5 O 0.75 and the second solid electrolyte Li3YCl6 are added to a ball mill in a glove box in a mass ratio of 1:1, wherein the melting point of the first solid electrolyte is 350°C, the melting point of the second solid electrolyte is greater than the melting point of the first solid electrolyte, the particle size D90 of the first solid electrolyte is 0.9μm, the particle size D90 of the second solid electrolyte is 0.3μm, the ratio of the particle size D50 of the first solid electrolyte to the particle size D50 of the second solid electrolyte is 3:1, and the rest is the same as Example 1.

[0133] Comparative Example 2

[0134] The preparation method of comparative example 2 is basically the same as that of comparative example 1, except that the hot pressing temperature is 60°C, that is, the mixture is placed in a hot pressing mold, and hot pressing is continued for 10 minutes under a pressure of 100 MPa and a temperature of 60°C to obtain a composite solid electrolyte membrane. The rest is the same as comparative example 1.

[0135] The relevant raw materials and process parameters in the preparation methods of Examples 1 to 17 and Comparative Examples 1 to 2 are listed in Table 1 below:

[0136] Table 1

[0137]

[0138] Test Case

[0139] The porosity, thickness, and ionic conductivity of the composite solid electrolyte membranes prepared in Examples 1 to 17 and Comparative Examples 1 to 2 were tested, and the battery internal resistance, discharge specific capacity, and volume energy density of the solid-state lithium-ion batteries prepared in Examples 1 to 17 and Comparative Examples 1 to 2 were tested. The test results are shown in Table 2. The test standards are as follows:

[0140] (1) Porosity test

[0141] True density test: The true density of the composite positive electrode is obtained by testing with a true density meter. The test process is as follows: After the power is turned on, the instrument is preheated according to the requirements of the instrument manual to ensure that the instrument reaches a stable working state. Place the sample to be tested in the sample pool, press the measurement button, and the instrument will automatically measure the density. After the measurement is completed, the instrument will automatically record the data and calculate the true density value ρ 真 .

[0142] Compacted density test: Add 100 mg of powder into a φ10 mm mold, apply a pressure of 375 MPa and maintain the pressure for 3 minutes, then remove the mold to obtain a compacted sheet, measure its thickness, and calculate its compacted density ρ 压实 .

[0143] Porosity: Porosity is (ρ 真 -ρ 压实 ) / ρ 真 .

[0144] (2) Thickness test

[0145] According to GB / T 6672-2001 standard, a Millimar C1208 film thickness gauge (Millimar C1208, manufactured by Millimar, Germany) was used to measure the thickness of the composite solid electrolyte membranes in Examples 1 to 17 and Comparative Examples 1 to 2.

[0146] (3) Electrolyte membrane conductivity test

[0147] At 25°C, the test structure of stainless steel sheet / solid electrolyte membrane / stainless steel sheet was used, the frequency range was 0.1Hz-7MHz, and the AC signal amplitude Z was 10 -2 The AC impedance test was carried out under the condition of V, and the ionic conductivity was calculated according to the formula σ=L / (S*R), where L is the thickness of the solid electrolyte membrane, S is the cross-sectional area of ​​the solid electrolyte membrane, and R represents the charge transfer resistance.

[0148] (4) Battery internal resistance test

[0149] The internal resistance of the solid-state lithium-ion batteries prepared in Examples 1 to 17 and Comparative Examples 1 to 2 was measured using a voltage internal resistance meter.

[0150] (5) Discharge specific capacity test

[0151] The solid-state lithium-ion batteries prepared in Examples 1 to 17 and Comparative Examples 1 to 2 were subjected to a capacity test. The batteries were left to stand for 1 min, and the discharge current was 0.1 C until the cut-off voltage was 2.7 V, and the first discharge capacity was recorded.

[0152] (6) Volume energy density test

[0153] The solid-state lithium-ion batteries prepared in Examples 1 to 17 and Comparative Examples 1 to 2 were placed in a 25°C ± 2°C thermostat for 30 minutes to reach a constant temperature. The solid-state lithium-ion batteries reaching a constant temperature were charged at a constant current of 0.5C to a full charge voltage, then charged at a full charge voltage constant voltage to a current of 0.05C, and discharged at 0.2C to a voltage of 3.0V, and the discharge energy was recorded.

[0154] Volume energy density = discharge energy / length of lithium-ion battery × width of lithium-ion battery × thickness of lithium-ion battery).

[0155] Table 2

[0156]

[0157] As can be seen from Table 1 and Table 2 above, the porosity of the composite solid electrolyte membranes of Examples 1 to 17 and the battery internal resistance of the solid-state lithium-ion battery are significantly lower than those of Comparative Examples 1 to 2, and the conductivity of the composite solid electrolyte membranes of Examples 1 to 17 and the capacity and volume energy density of the solid-state lithium-ion battery are significantly higher than those of Comparative Examples 1 to 2, indicating that compared with Comparative Examples 1 to 2, in Examples 1 to 17, during the hot pressing process of the mixture of the first solid electrolyte and the second solid electrolyte, the second solid electrolyte undergoes a phase change from a granular solid phase to a liquid phase with fluidity, and forms a continuous state of fluid under a certain pressure, and the first solid electrolyte particles are dispersed in the continuous structure of the second solid electrolyte. In the cooling step, the second solid electrolyte undergoes a phase change again to form a solid continuous structure different from the granular continuous structure, and a composite solid electrolyte membrane with lower porosity is prepared, and the ionic conductivity of the prepared composite solid electrolyte membrane is improved, so that the capacity and cycle performance of the solid-state battery prepared by the composite solid electrolyte membrane are optimized, and the battery internal resistance is further reduced.

[0158] It can be seen from Examples 1 to 5 that when the mass ratio and particle size ratio of the first solid electrolyte and the second solid electrolyte are within an appropriate range, the prepared composite solid electrolyte membrane can have a higher ionic conductivity, and the solid-state lithium-ion battery can have better capacity performance and cycle performance.

[0159] From Example 1, Example 6 to Example 11, and Comparative Example 1 to Comparative Example 2, it can be seen that when the temperature, time and pressure of the hot pressing treatment are within an appropriate range, the prepared composite solid electrolyte membrane can have a higher ionic conductivity, and the solid-state lithium-ion battery can have better capacity performance and cycle performance.

[0160] From Example 1 and Example 12 to Example 17, it can be seen that when the ball milling mixing speed, time and material ball ratio are within an appropriate range, the prepared composite solid electrolyte membrane can have a higher ionic conductivity, and the solid-state lithium-ion battery can have better capacity performance and cycle performance.

[0161] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0162] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. A method for preparing a composite solid electrolyte membrane, characterized in that: The method comprises: The first solid electrolyte and the second solid electrolyte are mixed to obtain a mixture; the first solid electrolyte includes an inorganic solid electrolyte, and the second solid electrolyte includes Li3MCl 6-x Br x , M is a trivalent metal ion, and x satisfies 0<x<6; Performing hot pressing treatment on the mixture and cooling it to obtain a composite solid electrolyte membrane; Wherein, the melting point T2 of the second solid electrolyte is 80°C to 200°C; The hot pressing temperature T0 of the hot pressing treatment is 80°C to 200°C; And satisfy: T0≥T2; Wherein, in the hot pressing step, the hot pressing temperature T0 and the melting point T1 of the first solid electrolyte satisfy: T1>T0.

2. The preparation method according to claim 1, characterized in that: During the hot pressing step, the second solid electrolyte undergoes a phase change from solid to liquid; and In the cooling step, the second solid electrolyte is transformed from a liquid state to a solid state.

3. The preparation method according to claim 1, characterized in that: M is selected from Ga 3+ 、In 3+ 、Al 3+ , Fe 3+ , Y 3+ 、Bi 3+ , one or more of the +3 valent lanthanide metals.

4. The preparation method according to claim 1, characterized in that: In the hot pressing step, the hot pressing time of the hot pressing treatment is 0.5min to 30min; and / or, The hot pressing pressure of the hot pressing treatment is 10MPa~500MPa.

5. The preparation method according to claim 1, characterized in that: In the cooling step, the mixed material is naturally cooled at room temperature.

6. The preparation method according to claim 1, characterized in that: The step of mixing the first solid electrolyte and the second solid electrolyte specifically includes weighing the first solid electrolyte and the second solid electrolyte according to a mass ratio, wherein the mass ratio of the first solid electrolyte to the second solid electrolyte is (95:5) to (20:80).

7. The preparation method according to claim 1, characterized in that: In the step of mixing the first solid electrolyte and the second solid electrolyte, the ratio of the particle size D50 of the first solid electrolyte to the particle size D50 of the second solid electrolyte is (1:5) to (10:1).

8. The preparation method according to claim 1, characterized in that: The mixing method of mixing the first solid electrolyte and the second solid electrolyte includes ball milling mixing, and the ball milling mixing satisfies at least one of the following conditions (1) to (3): (1) The rotation speed of the ball milling mixing is 100 rpm to 300 rpm; (2) The ball milling mixing time is 0.1h~2h; (3) The ball-to-material ratio of the ball milling mixture is (3:1) to (30:1).

9. A composite solid electrolyte membrane, characterized in that: It comprises a composite solid electrolyte membrane prepared by the preparation method according to any one of claims 1 to 8.

10. A solid-state lithium-ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet and a composite solid electrolyte membrane according to claim 9 or a composite solid electrolyte membrane prepared by the preparation method according to any one of claims 1 to 8, located between the positive electrode sheet and the negative electrode sheet.

Citation Information

Patent Citations

  • High-density solid electrolyte membrane for metal lithium secondary battery and preparation method of high-density solid electrolyte membrane

    CN113471518A

  • Method for preparing sulfide / oxide solid electrolyte with melon pulp structure by mechanical method

    CN117174991A